Hating Alison Ashley - Klein, Robin, 1936- (Camberwell, Victoria : Penguin Group (Australia), 2016)
'Utter loathing and hatred,' I said. 'I wouldn't even be on the same bus as you . . . If I could have caught a virus in time.' Erica Yurken knew she was destined for great things. Never in any doubt about her own genius, she felt superior to everyone at notorious Barringa East . . . that is, until Alison Ashley turned up.
Imprint: e-penguin.
First published by Penguin Books Australia Ltd, 1984.
For primary school age.
Keywords: Friendship -- Juvenile fiction; Envy -- Juvenile fiction; Jealousy -- Juvenile fiction; Romance & relationships stories (Children's / Teenage); Australian